Physico-Mechanical And Biological Evaluation Of Three-Dimensional Printed Thermoplastic Polyurethane And Polylactic Acid Scaffold For Tracheal Tissue Engineering - Samat, Asmak Abdul (2023)
Surgical restoration of extensive tracheal lesions is complicated, and it necessitates the use of a biocompatible, mechanically stable, and non-toxic material that degrades gradually to overcome the limitation of allografts. A three-dimensional (3D) printed tracheal scaffold produced from polymers is one option for addressing some of the challenges in tracheal transplantation. Polymer blending is one approach for creating material with specific properties for a trachea scaffold. The goal of this study was to evaluate the physical, mechanical, and biological properties of thermoplastic polyurethane (TPU) and polylactic acid (PLA) blend as prospective tracheal replacement materials. Both materials are well-known for their promising properties when utilised independently, thus broadly employed in various applications, especially in the biomedical field. It is hypothesised that combining the two materials and the subsequent 3D printing method produces a composite with suitable qualities for tracheal replacement. Different TPU and PLA compositions were melt-blended and characterised for their physical and mechanical properties,